Improving Third Year English Students’ Translation of Text Genres by Using The Method of Comparing the Position of Words in Phrases or Sentences in the Text Genres: https://doi.org/10.69692/journal2021.12.02 - SISOMBATH, Sithonh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This article presents an action research study undertaken at the Faculty of Education, Souphanouvong University during the 2020-2021 academic year. The aim was to determine whether teaching a method of comparing the position of words in the source language (English) and the target language (Lao) could improve third-year English students’ translation of text genres, and whether they were able to learn new vocabulary using this procedure. The sample comprised the 19 students from class 3ENT who studied English as their major. Research instruments included a pre-test, post-test, and questionnaire. Both pre-test and post-test consisted of English to Lao and Lao to English translation, and the questionnaire included 12 closed and open-ended questions. For the experimental method of teaching-learning translation, specific instruction for comparing the position of words between English and Lao was provided for three hours, followed by further practice in translating text genres for two hours per week over 16 weeks. This was implemented in-class and online. Finally, the pre-test and post-test scores of the 19 students were compared to see the difference in students’ translation ability. SPSS version 20 was used to calculate all the data. The results of this study showed the mean of the pre-test was 13.5263 with SD = 5.30585, and the mean of the post-test was 28.5263 with SD = 5.95696, while the t-test = -8.652 and p = 0.000. Before learning this technique for translation, 37% of students did not know how to translate English phrases or sentences into the Lao language by themselves, 47% of them knew a few ways, and 16% of students knew and understood how to use many techniques by themselves. After the experimental method was taught, 63% of students felt they knew how to translate English to Lao by themselves. In addition, 84% of students indicated they could learn new vocabulary from text genres, while 16% said they could learn a little new vocabulary from them.